2009
DOI: 10.1007/s12603-009-0100-3
|View full text |Cite
|
Sign up to set email alerts
|

Can dietary intervention help in management of problem behaviors in dementia?

Abstract: Behavioral symptoms of dementia are often more distressing to family caregivers than cognitive impairments and may lead to need for institutionalization. It is possible to distinguish two types of behavioral symptoms: disturbing and non-disturbing ( Fig. 1). The main non-disturbing symptom is apathy that the most common behavioral symptom in individuals with dementia (1) and is often not treated because apathetic individuals pose little problem for their caregivers. However, presence of apathy is decreasing qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Sunflower seeds are a high-Trp/protein food. The Trp content is 1.75 g/100 g protein, second only to milk and sesame ( 9 ). Our study confirmed that deoiled sunflower seeds high in Trp levels can improve the utilization of Trp and promote the synthesis of 5-HT in the brain, thereby improving behavioral disorders and depression in stressed mice ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sunflower seeds are a high-Trp/protein food. The Trp content is 1.75 g/100 g protein, second only to milk and sesame ( 9 ). Our study confirmed that deoiled sunflower seeds high in Trp levels can improve the utilization of Trp and promote the synthesis of 5-HT in the brain, thereby improving behavioral disorders and depression in stressed mice ( 10 ).…”
Section: Introductionmentioning
confidence: 99%